PENGEMBANGAN MEDIA SCRAPBOOK CUACA UNTUK PEMBELAJARAN PERUBAHAN CUACA KELAS III SEKOLAH DASAR - Agung Bayu Hari Seno (PT. Hasba Edukasi Mandiri, 2026)
Indonesian language instruction on weather changes and their impact on human life in third-grade elementary school still relies on lecture-based teaching methods and insufficient use of instructional media, resulting in students losing interest in the lessons and struggling to understand the material. Given this situation, this study aims to create an instructional medium in the form of a weather scrapbook that can effectively improve the quality of the teaching-learning process for the topic of weather changes and their impact on human life in third-grade elementary school. This study employed a Research and Development (R&D) approach using the ADDIE model, which consists of several stages: analysis, design, development, implementation, and evaluation. The research subjects consisted of 10 students in a pilot study and 22 students in a full-scale study in third-grade classes at SD Negeri 1 Gemenggeng, Nganjuk Regency. Data collection methods included observation, interviews, and questionnaires validated by media experts and subject matter experts; a practicality questionnaire completed by teachers; and tests to measure student learning outcomes. Data analysis was conducted using quantitative and qualitative descriptive methods to determine the levels of validity, practicality, and effectiveness of the developed media. The study showed that the weather scrapbook learning media had a very good level of validity. The media validation percentage reached 88%, which falls into the “highly valid” category, while the content validation percentage was 74%, which falls into the “valid” category. The practicality level averaged 93%, falling into the “highly practical” category, while the effectiveness level reached 86% in the limited trial and 93% in the large-scale trial, both falling into the “highly effective” category. Based on these results, the weather scrapbook learning medium is considered valid, practical, and effective, and can therefore be used as a learning tool to help third-grade elementary school students better understand material on weather changes and their impact on human life.